The online millionaire : strategies for building a web-based empire on eBay and beyond - Joyner, Amy (John Wiley & Son, Inc., 2007)
This book will show you how to become the next huge online success story. In The Online Millionaire, Amy Joyner introduce you to the most popular online channels and reveal the tricks of the trade for excelling in these marketplaces. You'll learn the ins and outs of selling on eBay, Amazon.com, Yahoo!, Overstock.com, and other auction marketplaces. Plus, you'll find out how to go about building your own professional e-commerce store, along with proven ways to make money promoting other companies on your site.